Relationship Between Self-Esteem and Negative Emotional State with Academic Procrastination in Final Level Students - Refirman Djamahar; Yulilina Retno Dewahrani; Resty Octaviani (Indonesian Journal of Biology Education, 2020)
Self-esteem and negative emotional state have a role in the tendency of students to do academic procrastination in completing the final assignments. This study aims to determine the relationship between self-esteem and negative emotional state with academic procrastination in last year's students — the research conducted at the Biology Education and Biology Department, Jakarta State University, in July 2019. The method used was descriptive correlational. The research sample was 48 Biology students from 2012, 2013, and 2014 who had not graduated on time selected by simple random sampling. The instruments used were the Coopersmith Self Esteem Inventory (CSEI), Depression Anxiety Stress Scale 42 (DASS 42), and academic procrastination questionnaires. The analysis prerequisite test results obtained by data distribution normally and homogeneously. The result is a significant relationship between self-esteem and negative emotional states with academic procrastination in final year college students.